2005
DOI: 10.1186/1472-6815-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of difficult airway in intratracheal tumor surgery

Abstract: Background: Tracheal malignancies are usual victim of delay in diagnosis by virtue of their symptoms resembling asthma. Sometimes delayed diagnosis may lead to almost total airway obstruction. For difficult airways, not leaving any possibility of manipulation into neck region or endoscopic intervention, femorofemoral cardiopulmonary bypass can be a promising approach. Case Presentation:We are presenting a case of tracheal adenoid cystic carcinoma (cylindroma) occupying about 90% of the tracheal lumen. It was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The symptoms with subglottic or tracheal tumor include prolonged cough and wheezing. It can be misdiagnosed as asthma (Garas and McGuirt, 2006;Dahm et al, 1998;Kokturk et al, 2005;Goyal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms with subglottic or tracheal tumor include prolonged cough and wheezing. It can be misdiagnosed as asthma (Garas and McGuirt, 2006;Dahm et al, 1998;Kokturk et al, 2005;Goyal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It usually becomes symptomatic when it starts occluding more than 75% of the lumen (Goyal et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Goyal et al 5 reported successfully treating a patient with a tracheal tumor occupying about 90% of the tracheal lumen by surgical excision under femoral-femoral CPB. Byrne et al 6 concluded that the planned use of CPB is safe for complete resection of thoracic malignancies and in the event of injury to vascular structures during tumor resection.…”
Section: Discussionmentioning
confidence: 98%
“…In case of complete tracheal blockage and severe breathing problems, extracorporeal membrane oxygenation should be considered. 6 8 Here, because the mass induced partial obstruction of the tracheal lumen and preoperative images showed its confinement within the endoluminal cavity of the trachea with no visible extra tracheal extension, anesthetic induction and placement of the endotracheal tube could be considered. There are two potential ways to insert the tube tip above or below the mass during anesthetic induction.…”
Section: Discussionmentioning
confidence: 99%